1977
DOI: 10.1063/1.323490
|View full text |Cite
|
Sign up to set email alerts
|

Influence of secondary-electron emission from MgO surfaces on voltage-breakdown curves in Penning mixtures for insulated-electrode discharges

Abstract: Voltage-breakdown curves in a Ne+0.1% Ar Penning mixture for insulated-electrode discharges are strongly influenced by changes in the surface properties of a deposited MgO cathode. A model has been developed to calculate an effective secondary-electron-emission coefficient γ in Penning mixtures as a function of the insulator-energy-band parameters. Incorporation of the calculated γ into the breakdown criterion results in good agreement between calculated and measured voltage-breakdown curves for differently pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…20,28 The information on the DOS of the valence band of MgO could be obtained from the energy distribution of the abnormal electrons, confirming that the present approach is effective for characterizing MgO films as a protective layer in PDPs.…”
Section: Discussionsupporting
confidence: 66%
“…20,28 The information on the DOS of the valence band of MgO could be obtained from the energy distribution of the abnormal electrons, confirming that the present approach is effective for characterizing MgO films as a protective layer in PDPs.…”
Section: Discussionsupporting
confidence: 66%
“…When the released energy of Ei-χ-E g S is transferred to another valence electron, and the energy of the excited electron exceeds the vacuum level, the electron escapes from the surface as a secondary electron, with typical E g S and electron affinity χ values of 6.3 and 0.85-1.0 eV, respectively. 29 In the case of Xe+ irradiation onto a defect-free MgO surface (Fig. 6(a)), because the difference between the energies of a valence electron in the MgO and the ionized shell in an Xe+ ion is lower than that required for secondary electron emission, the secondary electron will not be emitted at all.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that defects in the films could trap the excited secondary electrons leading to a decrease of the amount of the secondary electrons escaping from film surface and therefore to decrease of d. Cheng et al [149] reported that the d coefficient increases with increasing E/P, where E is the applied field and P is the pressure between the cells. This increase was judged by the photoemission and kinetic ejection mechanisms for SEE from a surface [193][194][195].…”
Section: Secondary Electron Emission Yieldmentioning
confidence: 99%